EXPLORING THE COMBINED EFFECT OF PRODUCT AVAILABILITY, PRICING, AND PROMOTION ON FEMALE CONSUMER RETENTION - Shikha, Farzana Arifin; Hoque, Ashikul; Hamid, Abu Bakar Abdul (Journal of Business Studies and Management Review, 2025)
This article investigates how promotional activities, strategic pricing, and product availability influence the retention of female consumers, a relatively underexplored domain in customer loyalty research. Recognizing that women represent a substantial share of global purchasing power, the study underscores the importance of understanding the factors that shape long-term female buyer engagement. A systematic review of existing literature, supported by industry-based analyses such as reports and case studies, was conducted to evaluate how these strategies affect consumer behavior. The findings reveal that transparent pricing, consistent product availability, and personalized promotional initiatives are key determinants of customer satisfaction and retention. The study is distinctive in highlighting the scarcity of women-cantered retention strategies within existing scholarship. It emphasizes the necessity for retailers to deliver seamless and tailored shopping experiences, as failure to do so may result in financial and reputational losses. From a practical standpoint, the research suggests that organizations should adopt data-driven insights and flexible promotional strategies to strengthen the loyalty of female consumers. Keywords: Female Consumers, Customer Retention, Product Availability, Psychological Pricing, Promotions, Loyalty Strategies